Is narcolepsy a classical autoimmune disease? (2015)
Narcolepsy is a neurological disorder characterized by excessive daytime sleepiness. It is caused by the loss of orexin producing neurons in the lateral hypothalamus. Current evidences suggest an autoimmune mediated process causing the specific loss of orexin neurons. The high association of the disease with the HLA DQB1?06:02, as well as the link with environmental factors and are important clues supporting this theory. Recently, the association between the occurrence of the disease and vaccination campaign after the 2009 H1N1 pandemic highlighted the importance to increase the knowledge in the Pandora box of the vaccines. This review discusses the last finding regarding the pathogenesis of the disease and its relationship with the H1N1 vaccines. © 2014 Elsevier Ltd. All rights reserved.